AB0478 Mild and moderate hepatic impairment have no clinically relevant impact on upadacitinib pharmacokinetics: results from a dedicated phase 1 study. (12th June 2018) - Mohamed, M.-E.F.; Coppola, S.; Feng, T.; Lacerda, A.P.; Othman, A.A.
Abstract : Background: Upadacitinib is a selective Janus kinase 1 (JAK1) inhibitor being developed for the treatment of several inflammatory diseases, including rheumatoid arthritis (RA). Upadacitinib efficacy was demonstrated in Phase 2 studies in RA, Crohn's disease, atopic dermatitis, in addition to three completed Phase 3 trials in RA. Upadacitinib is a non-sensitive substrate for hepatic metabolism by cytochrome P450 3A; however, 38% and 24% of upadacitinib immediate-release dose are eliminated unchanged in faeces and urine, respectively. Since, there is a potential for upadacitinib use in some patients with hepatic impairment, evaluation of impact of hepatic impairment on upadacitinib exposure is of key clinical relevance. Doses of 15 mg and 30 mg once daily (QD) using upadacitinib extended-release formulation have been evaluated in Phase 3 trials in RA. Objectives: To evaluate the effect of mild and moderate hepatic impairment on the pharmacokinetics of upadacitinib. Methods: This was a Phase 1, open-label study in subjects with mild (n=6) or moderate (n=6) hepatic impairment, according to the Child-Pugh classification, and demographically-matched healthy subjects (n=6). Subjects received a single 15 mg dose of upadacitinib extended-release formulation under fasting conditions. Blood samples for upadacitinib assay were collected over 120 hours after administration. Upadacitinib maximum observed plasma concentration (Cmax ), area under the plasma concentration curve (AUC), and terminal phase elimination half-life (t1/2 ) were calculated using non-compartmental analyses. Analyses of covariance were conducted to estimate upadacitinib exposure in subjects with hepatic impairment relative to subjects with normal hepatic function. Results: There was no statistically significant difference in upadacitinib Cmax or AUC in subjects with mild and moderate hepatic impairment compared to subjects with normal hepatic function. One subject with moderate hepatic impairment showed significantly lower upadacitinib exposures than subjects with normal hepatic functions and was excluded as an outlier to ensure a conservative estimate for effect of hepatic impairment on exposure. Upadacitinib exposure ratio central values [and 90% confidence intervals] in subjects with mild and moderate hepatic impairment were 1.28 [0.91–1.79] and 1.24 [0.87–1.76] for AUC and 1.04 [0.77–1.39] and 1.43 [1.05–1.95] for Cmax, respectively, compared to subjects with normal hepatic function. Upadacitinib terminal elimination half-life (harmonic mean ±pseudo standard deviation) was 7.99±4.60 and 4.14±1.46 in subjects with mild and moderate hepatic impairment relative to 8.93±4.87 in subjects with normal hepatic function. Upadacitinib was generally well tolerated by the subjects in the study. Conclusions: Mild and moderate hepatic impairment result in only a very limited effect on upadacitinib plasma exposures (<30% increase in upadacitinib AUC). Therefore, in clinical trials, dose adjustments in subjects with mild or moderate hepatic impairment are not warranted. Acknowledgements: The studies presented were funded by AbbVie. AbbVie contributed to the study design, research, and interpretation of data, reviewing, and approving the publication. All authors are employees and shareholders of AbbVie. Disclosure of Interest: M.-E. Mohamed Shareholder of: AbbVie, Employee of: AbbVie, S. Coppola Shareholder of: AbbVie, Employee of: AbbVie, T. Feng Shareholder of: AbbVie, Employee of: AbbVie, A. P. Lacerda Shareholder of: AbbVie, Employee of: AbbVie, A. Othman Shareholder of: AbbVie, Employee of: AbbVie